A compatible configuration strategy for burner streams in a 200 MWe tangentially fired oxy-fuel combustion boiler. (15th June 2018) - Guo, Junjun; Liu, Zhaohui; Hu, Fan; Li, Pengfei; Luo, Wei; Huang, Xiaohong
Highlights: Compatible configuration strategy for tangential oxy-burners is firstly proposed. Momentum ratio criterion for tangentially fired oxy-combustion is illustrated. Temperature deviation is reduced by using opposing tangential stream technology. Temperature deviation and CO level are decreased by approximately 65% and 90%. Abstract: The configurations of burner streams under oxy-fuel combustion are highly affected by its increased initial oxygen level. In this study, an air combustion and oxy-fuel combustion compatible configuration strategy for burner streams is proposed for a 200 MWe tangentially fired boiler, by aid of numerical simulation. Firstly, to achieve a momentum of primary and secondary streams that is similar to that of air combustion, the tertiary stream is switched-off in oxy-fuel combustion. In addition, the opposing tangential primary stream technology is suggested to reduce the gas temperature deviation in the upper furnace, which affects the quality of the steam and the safe operation of the boiler. For the present study, the appropriate opposing tangential angle is 5°–7° relative to the original primary stream design, and the ratio of opposing tangential momentum flow moment should be controlled at the low limit of 0.8 to decrease gas temperature deviation. To achieve a supported flame by the secondary stream, the momentum of the bottom secondary stream in oxy-fuel combustion should not be less than that in air combustion. The study illustrates for the first time that, the key design features of tangentially fired burners under oxy-fuel combustion. Although there are significant changes in the oxidant volume, oxidant composition, and chemical reaction under oxy-fuel combustion conditions, the design criteria of oxy-fuel tangentially fired boiler, in terms of momentum of the primary stream, momentum of the bottom secondary stream, and momentum ratio and momentum flow moment ratio of the secondary stream to primary stream, are consistent with those under air combustion.